2018
DOI: 10.1016/j.biotechadv.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Host cell protein removal from biopharmaceutical preparations: Towards the implementation of quality by design

Abstract: Downstream processing of protein products of mammalian cell culture currently accounts for the largest fraction of the total production cost. A major challenge is the removal of host cell proteins, which are cell-derived impurities. Host cell proteins are potentially immunogenic and can compromise product integrity during processing and hold-up steps. There is an increasing body of evidence that the type of host cell proteins present in recombinant protein preparations is a function of cell culture conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 153 publications
1
37
0
Order By: Relevance
“…Calculated p ‐values for ANOVA comparisons of each peptide resin compared to both benchmark resins (Capto Q and Capto Adhere) are provided. Species identified by shotgun proteomics in this study identified as “problematic” based on prior art (Aboulaich et al, ; Bailey‐Kellogg et al, ; Chiu et al, ; Fischer et al, ; Gagnon et al, ; Goey et al, ; Jawa et al, ; Levy et al, ; Mechetner et al, ; Zhang et al, ). * p < .05.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Calculated p ‐values for ANOVA comparisons of each peptide resin compared to both benchmark resins (Capto Q and Capto Adhere) are provided. Species identified by shotgun proteomics in this study identified as “problematic” based on prior art (Aboulaich et al, ; Bailey‐Kellogg et al, ; Chiu et al, ; Fischer et al, ; Gagnon et al, ; Goey et al, ; Jawa et al, ; Levy et al, ; Mechetner et al, ; Zhang et al, ). * p < .05.…”
Section: Resultsmentioning
confidence: 82%
“…The application of proteomics‐based approaches at different stages of mAb production has revealed new challenges related to the removal of the host cell protein (HCP) impurities secreted by the mAb‐expressing cells. In a recent review of HCP removal strategies, Goey, Al huthali, and Kontoravdi () presented a thorough survey of HCPs that pose a significant risk to patient's health, and highlighted the challenges that mAb manufacturers face in ensuring rigorous HCP clearance. The authors recommend that upstream process conditions be controlled to minimize downstream bottlenecks and challenges, including high product titers as well as high HCP levels that accompany them.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations